Numerical Analysis of TBM Tunnel Lining Behavior using Shotcrete Constitutive Model - Shaalan, Heyam H.; Azit, Romziah; Mohamad Ismail, Mohd Ashraf (Civil Engineering Journal, 2018)
Shotcrete is a fundamental support element for tunnels and underground constructions. Shortly after application, shotcrete linings undergo a high load while the ordinary concrete is not fully hardened yet. Therefore, the time-dependent behaviour of the shotcrete material must consider. Traditional approaches assume a linear elastic behaviour using a hypothetical young modulus to model this time-dependency and creep effects. In this paper, a new constitutive model of shotcrete is applied to evaluate the time-dependent behaviour of TBM tunnel lining under high in-situ stress state. The Shotcrete model is based on the framework of Elasto-plasticity and designed to account for non-linear and time-dependent behaviour for concrete material more realistically. A parametric study of the time-dependent behaviour of the shotcrete lining, using the shotcrete model, is performed. To achieve this, the influence of the lining thickness, tunnel diameter and tunnel depth on the development of the stresses and displacement of the shotcrete lining with time is investigated. The results showed that the development of the lining tensile stress with time at tunnel crown increases by increasing the lining thickness and tunnel depth, whereas it decreases by increasing of the tunnel diameter. At the tunnel sidewall, the lining compression stress with time increases with the increase of the tunnel depth and diameter, while higher lining thickness decreases the lining compressive stresses. However, the results showed the ability of the shotcrete model to simulate the structural behaviour of the shotcrete lining with time.